Integrated modeling of EM response functions from Peninsular India and Bay of Bengal - Arora, B.R.; Subbarao, P.B.V. (My University, 2002)
Existing sets of magnetovariational data from the large numbers of sites distributed across the peninsular India and those in the Bay of Bengal are reanalysed to obtain inter-site vertical and horizontal field transfer functions. Maps of induction arrows relocate the earlier reported conductive zones beneath the Palk-Strait and a regional scale anomaly in the offshore region, immediately southwest of the southern tip of Indian Peninsula, named South India Offshore Conductivity Anomaly (SIOCA). Period dependence of the induction arrows suggests that with increasing period SIOCA tends to control the induction pattern over the entire peninsula. Presentation of the horizontal transfer functions in the form of ellipses of anomalous currents helps to characterize the period and spatial behaviour of horizontal fields at seafloor sites. Integrated thin sheet modeling of the on-land and seafloor induction features suggest that the greater part of the anomalous behaviour of the horizontal fields at seafloor sites can be attributed to the shielding effects due to seawater. The weak anisotropic behaviour of the horizontal fields at selected sites can be explained in terms of the concentration of the induced currents in the sediment filled troughs on either side of the 85°E Ridge. Several lines of geophysical evidence favour the hypothesis that SIOCA, low velocity zone, low magnetization anomaly, all centered near the southern tip of the India, are the relics of the interaction of Marion Plume outburst with Indian lithosphere.
Keywords: EM response functions; Integrated modeling; Magnetovariational data; Lithosphere